Comparing outcomes of stereotactic body radiotherapy with intensity-modulated radiotherapy for patients with locally advanced unresectable pancreatic cancer. Issue 3 (March 2015) - Lin, Jang-Chun; Jen, Yee-Min; Li, Ming-Hsien; Chao, Hsing-Lung; Tsai, Jo-Ting
<x xml:space="preserve">Abstract</x> Objectives Survival in patients with locally advanced unresectable pancreatic cancer (LAUPC) is poor, and local recurrence continues to be a major problem in the management of this disease. Radiotherapy (RT) using different RT techniques, including intensity-modulated radiotherapy (IMRT) and stereotactic body radiation therapy (SBRT), may lead to different clinical outcomes for patients with LAUPC. Here, we compared SBRT with IMRT for patients with LAUPC with respect to survival rate, local control (LC) rate, and toxicity-related dose distribution. Materials and methods This retrospective study from March 2007 to March 2011 included 41 patients with LAUPC who were divided into two groups, with 20 patients receiving SBRT and 21 patients receiving IMRT. The median follow-up time was 16 months. Results For the IMRT and SBRT groups, the median survival times were 13 and 20 months, and 1-year overall survival (OS) rates were 70.7 and 80.0%, respectively. There was no difference in OS between the two RT techniques. RT with SBRT showed significantly better local disease-free survival than IMRT for patients with LAUPC. Tobacco use had a borderline effect on LC. Thus, further statistical analysis showed that patients who used tobacco had better LC after receiving SBRT than IMRT. Conclusion SBRT improved LC for LAUPC patients and had similar radiation toxicity compared with IMRT. Further study is required to define the effects of administered radiation dose and fractionation, as well as to further expand the sample size, to use a prospective study, and to observe the long-term efficacy of these techniques.